Foreign exchange rate - Central Bank of Nigeria, Research Department (Abuja, Nigeria Central Bank of Nigeria, 2016)
Gives better understanding of the exchange rate and its variants using the simplest language.
Includes bibliographical references.
oif 05/06/17
Ref.
Keywords: Foreign Exchange; Exchange rates